Hearing Difficulty and Risk of Mortality. (July 2019) - Lin, Harrison W.; Mahboubi, Hossein; Bhattacharyya, Neil
Objective: Investigate whether hearing difficulty has an influence on the risk of mortality. Methods: A nationally representative sample of individuals 18 years or older with data available for hearing and mortality status was selected from the National Health Interview Surveys (NHIS) 2005-2009. Self-perceived hearing status was regrouped as excellent/good, a little to moderate trouble, a lot of trouble, and deaf. Other independent variables investigated were demographics and comorbidities. Univariate analysis was performed to calculate the incidence of mortality, and 95% confidence intervals (CI) and multivariate analysis adjusted for demographics and comorbidities was performed to calculate odds ratios (OR) of mortality. Those with excellent/good hearing were considered as reference for ORs. Results: Of 215.6 million Americans (mean age = 45.9 years; 51.7% female), approximately 16.0% (95% CI, 15.6%-16.3%) considered their hearing less than excellent or good. The 5-year mortality rate was 4.2% (95% CI, 4.0%-4.3%). In the univariate analysis, the mortality rate increased with the degree of hearing difficulty from 3.0% in excellent/good hearing to 19.5% in a lot of trouble hearing and 17.8% in deaf. With multivariate analysis, adjusted ORs of mortality were 1.5 (95% CI, 1.3-1.7) in those who had a lot of trouble hearing and 1.6 (95% CI, 1.1-2.3) in those who were deaf. Conclusion: Hearing difficulty may be associated with an increased risk of mortality, and this risk may correlate with the degree of hearing difficulty.